Tingkat Keberhasilan Penggunaan Pupuk Hayati Bioboost dan Interval Pemberian terhadap Pertumbuhan dan Produksi Tanaman Mentimun (Cucumis sativus L.) - Karim, Harli A.; Nurdin, Dahlia; Enice, Enice (Universitas Khairun, 2022)
This research was conducted in Timoro Village, Tabulahan Subdistrict, Mamasa Regency, which was conducted in April to July 2019. The aim was to determine the level of success in using Bioboost biofertilizers and the interval of administration of growth and production of cucumber plants. The design method used in the implementation of this study was in the form of a Randomized Group Design with a Separate Plot Design (RPT) pattern. Main plot of Bioboost (W) biological fertilizer time interval treatment includes two levels, namely: W1 = Bioboost Biofertilizer Giving biweekly W2 = Bioboost Biofertilizer giving once every three weeks Whereas Child Plot (AP) is a dose of Bioboost (F) consisting of bioboost fertilizer (F) consisting of the three levels, namely: F0 = without administration of Bioboost Biofertilizer F1 = dose of Bioboost Biofertilizer 20 ml + 1000 ml of water. F2 = dosage of Bioboost 40 ml + 1000 ml water.The results showed that the interaction of the time interval of administration with the dose of bioboost biofertilizer (Z x F) had no effect on the growth and production of cucumber plants on all parameters.Ã‚Â Keywords: Bioboost Biofertilizer, Giving and Cucumber Intervals